2017
DOI: 10.1002/hbm.23628
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Abnormalities in Idiopathic Parkinson's Disease: Evaluation by Diffusional Kurtosis Imaging and Neurite Orientation Dispersion and Density Imaging

Abstract: Mapping gray matter (GM) pathology in Parkinson's disease (PD) with conventional MRI is challenging, and the need for more sensitive brain imaging techniques is essential to facilitate early diagnosis and assessment of disease severity. GM microstructure was assessed with GM-based spatial statistics applied to diffusion kurtosis imaging (DKI) and neurite orientation dispersion imaging (NODDI) in 30 participants with PD and 28 age- and gender-matched controls. These were compared with currently used assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 93 publications
3
92
0
Order By: Relevance
“…Both ICVF and INVF have been proposed as biomarkers of highly anisotropic structures, such as neurons nuclei and glia, as suggested by previous studies on multiple sclerosis, 35 Alzheimer disease, 36 and Parkinson disease. 37 The within-lesion decreases are concordant with altered extracellular diffusion and increased extra-neurite volume measures performed on histology samples from surgical resections. 38 Those phenomena could also reflect the formation of additional diffusion barriers that may arise from loss of cortical stratification, deposits of extracellular matrix molecules, or F I G U R E 3 Multiple comparison test on the mean ranks of the image scores.…”
Section: Quantitative Lesion Profilingmentioning
confidence: 55%
See 1 more Smart Citation
“…Both ICVF and INVF have been proposed as biomarkers of highly anisotropic structures, such as neurons nuclei and glia, as suggested by previous studies on multiple sclerosis, 35 Alzheimer disease, 36 and Parkinson disease. 37 The within-lesion decreases are concordant with altered extracellular diffusion and increased extra-neurite volume measures performed on histology samples from surgical resections. 38 Those phenomena could also reflect the formation of additional diffusion barriers that may arise from loss of cortical stratification, deposits of extracellular matrix molecules, or F I G U R E 3 Multiple comparison test on the mean ranks of the image scores.…”
Section: Quantitative Lesion Profilingmentioning
confidence: 55%
“…Similarly, we found significant INVF decrease in suspected and confirmed FCD lesions. Both ICVF and INVF have been proposed as biomarkers of highly anisotropic structures, such as neurons nuclei and glia, as suggested by previous studies on multiple sclerosis, Alzheimer disease, and Parkinson disease . The within‐lesion decreases are concordant with altered extracellular diffusion and increased extra‐neurite volume measures performed on histology samples from surgical resections .…”
Section: Discussionmentioning
confidence: 66%
“…Studies implementing the NODDI model in PD have shown reduced Vic in the substantia nigra (Kamagata et al, ), and reduced Vic along the pathway in which seeds are placed in the substantia nigra and globus pallidus (Andica et al, ). In a study using automated analysis of many regions (not including substantia nigra though), the authors found increases in Viso in the left and right caudate, and left putamen (Kamagata et al, ). Other studies have reported significant differences between PD and healthy control subjects in other brain regions using conventional diffusion tensor imaging measures (e.g., FA, mean diffusivity, and axial diffusivity); however, these results have also been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, a biophysical model approach was developed in which model parameters, such as axonal volume fraction and compartmental diffusivities, are estimated from the measured diffusion MRI signal. To date, many such models have been proposed and used in clinical and experimental studies . However, it is emphasized that so far no definite consensus has been reached on how to parameterize the complex brain microstructure .…”
Section: Introductionmentioning
confidence: 99%